Percutaneous endoscopic gastrostomy – a simple solution to a complex problem - Wolak, Przemysław; Skiba, Renata; Niedziela, Wojciech (Medical Studies/Studia Medyczne, 2016)
Percutaneous endoscopic gastrostomy (PEG) was performed for the first time in the world on 12 June 1979. At present, the method of using gastrostomy has almost entirely superseded classical methods, which is related with its simplicity, lower costs, lack of need for hospital stay (PEG is often placed in ambulatory conditions) or a shorter period of hospitalisation, as well as a smaller number of complications compared to classical methods. The indications for gastrostomy are possibilities of feeding directly into the gastrointestinal tract, avoiding the oral cavity, throat, and oesophagus (for various reasons), or decompression of the gastrointestinal tract in the case of its obstruction as a palliative procedure. Gastrostomy may be performed by a classical open technique or by laparoscopic or endoscopic methods. Percutaneous endoscopic gastrostomy is the most common form of gastrostomy.